A horizontal plug-flow baffled bioelectrocatalyzed reactor for the reductive decolorization of Alizarin Yellow R. (November 2015) - Sun, Qian; Li, Zhiling; Wang, Youzhao; Cui, Dan; Liang, Bin; Thangavel, Sangeetha; Chung, Jong Shik; Wang, Aijie
Highlights: A plug-flow baffled bioelectrocatalyzed reactor (PFB-BER) was constructed. Membrane-less design of PFB-BER resulted in a low internal resistance. Effects with different HRT and number of electrode assembly were evaluated. PFB-BER showed superior Alizarin Yellow R (AYR) decolorization performance. Abstract: An application-oriented membrane-free, continuous plug-flow baffled bioelectrocatalyzed reactor (PFB-BER), was designed and testified for the decolorization of Alizarin Yellow R. Decolorization efficiency (DE) with an external power source of 0.5 V was higher than without electrolysis, i.e. 93.4% versus 73.6% (HRT of 24 h). Product formation efficiencies of p-phenylenediamine and 5-aminosalicylic acid were above 95% and 50%, respectively. When HRT decreased to 8 h and 4 h, DE reduced to 69.9% and 44.9%, respectively. An additional electrode assembly improved DE to 96.4% (HRT of 8 h) and 80% (HRT of 4 h), while energy consumption (HRT of 4 h) was lower than that of HRT of 12 h with single electrode assembly under comparable DE. The PFB-BER with higher removal capacity, lower internal resistance and energy consumption provides a new solution to treat the high loading azo dye-containing wastewaters.